2008
DOI: 10.1177/1934578x0800300726
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Compounds for Thrips Control – a Review

Abstract: This review covers aspects of putting essential oil compounds to use either as allelochemicals that manipulate the host selection process of Thysanopteran pest species or as botanical insecticides that kill these pests. Thysanoptera (thrips) make an especially interesting case study in this field, because their increasing economic impact puts some urgency on the development of novel control strategies, especially strategies that incorporate natural compounds. Known facts about the host selection behaviour of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 80 publications
(115 reference statements)
0
45
0
Order By: Relevance
“…Although their results showed the potential of using a push-pull strategy, they remarked on the need to identify a suitable semiochemicals which have activity against western ßower thrips but not biological control agents. Although rosemary (Rosmarinus officinalis L.) leaves and volatiles were repellent in their study, rosemary oil is rich in cineole, and it has been observed previously that cineole could be an attractant to western ßower thrips (Koschier 2008). Presumably, the repellency of the essential oil from a particular plant species is inßuenced not only by variations in chemical constituents that are known to vary geographically but also according to the speciÞc volatile concentration perceived by the insect.…”
Section: Proportion (Se Number Of Dishes and Total Thrips) Of Allmentioning
confidence: 95%
See 2 more Smart Citations
“…Although their results showed the potential of using a push-pull strategy, they remarked on the need to identify a suitable semiochemicals which have activity against western ßower thrips but not biological control agents. Although rosemary (Rosmarinus officinalis L.) leaves and volatiles were repellent in their study, rosemary oil is rich in cineole, and it has been observed previously that cineole could be an attractant to western ßower thrips (Koschier 2008). Presumably, the repellency of the essential oil from a particular plant species is inßuenced not only by variations in chemical constituents that are known to vary geographically but also according to the speciÞc volatile concentration perceived by the insect.…”
Section: Proportion (Se Number Of Dishes and Total Thrips) Of Allmentioning
confidence: 95%
“…The concentrated population of the pest facilitates control (Cook et al 2007). This strategy is considered to have most potential in high-value horticultural production in enclosed environments (Cook et al 2007, Koschier 2008.…”
Section: Proportion (Se Number Of Dishes and Total Thrips) Of Allmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the insecticidal or repellent activity of essential oils derived from plants within the family Lamiaceae have shown their potential against several insect pests (Hori ; Tunc and Sahinkaya ; Choi et al. ; Sedy and Koschier ; Akhtar and Isman ; Koschier ; Sajfrtova et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Integrating the biological activity of secondary plant compounds as botanicals that kill pests or reduce their fitness or as allelochemicals that modify pest behaviour in conventional pest control strategies might mitigate this problem. Moreover, they can become interesting synergists for various biological control measures in integrated or organic farming systems in the future (Chiasson et al 2004;Kornherr et al 2005;Cook et al 2007;Isman 2008;Koschier 2008). Many aromatic plants produce secondary plant compounds as part of their biochemical defence system against herbivorous insects.…”
Section: Introductionmentioning
confidence: 99%